2016
DOI: 10.54386/jam.v18i1.905
|View full text |Cite
|
Sign up to set email alerts
|

Performance of radiation-based reference evapotranspiration equation developed for Indian sub-humid conditions

Abstract: In this study, asite-specific radiation based equation for estimating reference evapotranspiration (ETo) was developed and its performance was statistically analysed in comparison to widely accepted FAO Penman-Monteith (FAO-56 PM) model and four radiation-based ETo methods for sub-humid Hazaribagh region of Jharkhand state. The equation was developed with daily values of incoming solar radiation in conjunction with air temperature (minimum and maximum) by considering daily FAO-56 PM ET0 values as index with we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…These limitations have made popular the use of either radiation-or temperature-based methods that require less climatic data than the Penman-Monteith equation. With respect to reference evapotranspiration (ETo), it has been demonstrated that radiation-based models could be developed with just solar radiation and air temperature data in sub-humid climatic conditions of developing countries where availability and reliability of weather data remains a problem, and that such local models could be give more reliable estimates under these conditions than other more popular radiation-based models (Tomar, 2016).…”
Section: Indirect Methodsmentioning
confidence: 99%
“…These limitations have made popular the use of either radiation-or temperature-based methods that require less climatic data than the Penman-Monteith equation. With respect to reference evapotranspiration (ETo), it has been demonstrated that radiation-based models could be developed with just solar radiation and air temperature data in sub-humid climatic conditions of developing countries where availability and reliability of weather data remains a problem, and that such local models could be give more reliable estimates under these conditions than other more popular radiation-based models (Tomar, 2016).…”
Section: Indirect Methodsmentioning
confidence: 99%